2020
DOI: 10.3390/ijerph17082896
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Performance of Public Sector Health System on Quality of Life in China: Evidence from the CGSS2015

Abstract: The determinants of quality of life can be social, economic, cultural, and governmental, to name a few. Prior research has shown that demographic factors and social support can have a significant impact on an individual’s quality of life. This research attempts to examine the effects of public sector health system performance on individuals’ quality of life in China, measured by (1) self-reported health, (2) depressed mood, and (3) happiness. The targeted population was individuals aged 18 and above. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This study has the following shortcomings, including the fact that although the indicator of perceived depression in this paper is also widely used in the existing literature, [106][107][108][109][110] it may not be the most effective measure of depression. To enhance the study's findings, it would be beneficial to incorporate other depression indexes based on more reliable scales, as this would enable a more comprehensive understanding of depression within the context of the study, leading to more accurate and reliable conclusions.…”
Section: Limitationmentioning
confidence: 99%
“…This study has the following shortcomings, including the fact that although the indicator of perceived depression in this paper is also widely used in the existing literature, [106][107][108][109][110] it may not be the most effective measure of depression. To enhance the study's findings, it would be beneficial to incorporate other depression indexes based on more reliable scales, as this would enable a more comprehensive understanding of depression within the context of the study, leading to more accurate and reliable conclusions.…”
Section: Limitationmentioning
confidence: 99%
“…The dependent variable of interest in this paper was the public satisfaction with their living conditions. Although prior research has begun to explore public life satisfaction using social media data in recent years [ 18 ], relying on the respondents’ self-reported life satisfaction remains the mostly common choice by current academics [ 70 , 71 ]. In line with the current research, we captured life satisfaction with one question in CSS2019 described as “How satisfied are you with your current life in general?”.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, some scholars have studied the efficiency of basic public services provision. Cuadrado analysed the impact of functional decentralisation and externalisation processes in 129 municipalities in Spain on the efficiency of local government public services provision (Sun and Li, 2020). Buchanan analysed the efficiency of rural public goods supply in the USA, and the results showed that an increase in the level of resident income contributes to the improvement of the efficiency of public goods supply (Buchanan, 1950a).…”
Section: Literature Reviewmentioning
confidence: 99%